Acute Q Fever in an Ankylosing Spondyloarthritis Patient Treated with Etanercept - Guiga, A.; Khalifa, D.; Ben Yahia, W.; El Amri, N.; Atig, A.; Ghannouchi, N. (Case Reports in Rheumatology, 2021)
Q fever is a rare zoonotic infection caused by Coxiella burnetii. Tumor necrosis factor-alpha (TNF-α) has an important role in the early control of this infection. However, TNF-α blockers increase the risk of infectious diseases. We present herein a patient who developed acute Q fever under anti-TNF-α who had a good evolution after anti-TNF stoppage and treatment with doxycycline.